POLITICAL PEOPLE OF THE USA - Karimova Robiyaxon; Abdurakhmanov Turakhon Saydullayevich (TADQIQOTLAR, 2025)
Annotation:This article provides a comprehensive overview of the key political figures in the United States, their roles, responsibilities, and influence on national and international affairs. It examines the hierarchy of political positions in the U.S. government and highlights prominent individuals who have shaped the political landscape throughout history. The article also explores how these figures impact policymaking, diplomacy, and the democratic process.